Design of a Photo Essay as an Educational Medium on the Influence of Self-Insecurity on Body Image - Luinika, Zefanya Tesa; Iqbal, Muhammad (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2025)
Adolescents are the most vulnerable age group to experience body image insecurity due to social pressure and unrealistic beauty standards promoted by media and society. This photographic essay project aims to represent the negative impacts of such insecurity through a visual medium. The methodology includes literature review and in-depth interviews with individuals who have personal experiences related to body image issues. Findings reveal that negative body perception can lead to psychological problems such as anxiety, depression, and eating disorders. Through a visual storytelling approach, this project conveys the emotions, body language, and internal conflicts experienced by the subjects. The conclusion of this design project highlights photography as an effective educational and reflective medium that can raise awareness, portray complex psychological realities, and foster empathy toward mental health and body image issues.